2020
DOI: 10.1055/s-0040-1715571
|View full text |Cite
|
Sign up to set email alerts
|

Improved Component Placement Accuracy with Robotic-Arm Assisted Total Knee Arthroplasty

Abstract: Component position of total knee arthroplasty (TKA) has been shown to influence prosthetic survivorships and clinical outcomes. Our objective was to compare the three-dimensional accuracy to plan of robotic-arm assisted TKA (RATKA) with conventional TKA for component position. We conducted a nonrandomized, prospective study comparing 143 RATKA with 86 conventional TKA operated at four U.S. centers between July 2016 and October 2018. Computed tomography (CT) scans obtained approximately 6 weeks postoperatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…These may have introduced bias into the analysis. 3 Evidence for implant accuracy PCOR Posterior condylar offset ratio, ISI Insall-Salvati Index, mTKA manual total knee arthroplasty, RATKA Robotic-arm assisted total knee arthroplasty Component accuracy Kayani et al [20] 2019 [Accuracy in achieving the planned implant positions compared to conventional jig based TKA] Mechanical alignment (degrees), mean (SD) mTKA 3.2 ± 1.2 vs RATKA 1.5 ± 0.9, p < 0.001 PCOR mTKA 0.3 ± 0.1 vs RATKA 0.2 ± 0.1, n.s Posterior slope mTKA 3.4 ± 1.1 vs RATKA 1.4 ± 0.6, p < 0.001 Joint line mTKA 2.9 ± 1.4 vs RATKA 1.0 ± 0.6, p < 0.001 Femur coronal mTKA 4.1 ± 1.1 vs RATKA 1.0 ± 0.4, p < 0.001 Femur sagittal mTKA 4.2 ± 0.8 vs RATKA 2.1 ± 0.7, p < 0.001 Tibia coronal mTKA 3.6 ± 0.8 vs RATKA 1.0 ± 0.5, p < 0.001 Tibia sagittal mTKA 3.9 ± 1.0 vs RATKA 2.0 ± 0.6, p < 0.001 Mahoney et al [28] 2020 Coronal positions measured via CT (mean ± SD)…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These may have introduced bias into the analysis. 3 Evidence for implant accuracy PCOR Posterior condylar offset ratio, ISI Insall-Salvati Index, mTKA manual total knee arthroplasty, RATKA Robotic-arm assisted total knee arthroplasty Component accuracy Kayani et al [20] 2019 [Accuracy in achieving the planned implant positions compared to conventional jig based TKA] Mechanical alignment (degrees), mean (SD) mTKA 3.2 ± 1.2 vs RATKA 1.5 ± 0.9, p < 0.001 PCOR mTKA 0.3 ± 0.1 vs RATKA 0.2 ± 0.1, n.s Posterior slope mTKA 3.4 ± 1.1 vs RATKA 1.4 ± 0.6, p < 0.001 Joint line mTKA 2.9 ± 1.4 vs RATKA 1.0 ± 0.6, p < 0.001 Femur coronal mTKA 4.1 ± 1.1 vs RATKA 1.0 ± 0.4, p < 0.001 Femur sagittal mTKA 4.2 ± 0.8 vs RATKA 2.1 ± 0.7, p < 0.001 Tibia coronal mTKA 3.6 ± 0.8 vs RATKA 1.0 ± 0.5, p < 0.001 Tibia sagittal mTKA 3.9 ± 1.0 vs RATKA 2.0 ± 0.6, p < 0.001 Mahoney et al [28] 2020 Coronal positions measured via CT (mean ± SD)…”
Section: Discussionmentioning
confidence: 95%
“…Future well-powered studies should report on the knee alignment and balancing techniques utilised in RATKAs to enable greater comparisons to be made on which techniques maximally benefit patient outcomes and provide better insights into alternate alignment philosophies. Bhimani et al [4] 2020 RATKA: to achieve the desired bone cuts and target limb alignment, along with symmetrically balanced flexion and extension gaps Unknown which technique and which reference alignment was utilised mTKA: A gap balancing technique was utilized using a ligamentous tensioning device with the extension gap balanced followed by balancing the flexion gap after release of the posterior cruciate ligament Gap balancing techniques utilised Kayani et al [18] 2018 mTKA utilised a measured resection technique aligned to the mechanical axis RATKA utilised dynamic referencing to achieve equal gaps throughout the range of motion, utilising gap balancing and kinematic alignment techniques Kayani et al [19] 2018 RATKA: intraoperative dynamic gap balancing techniques were used with kinematic alignment assessed through the arc of motion, and enabled fine tuning of implant positioning based on laxity of the soft tissue envelope, within 2 mm of the planned bone resection Utilised restricted kinematic alignment techniques mTKA: measured resection and mechanical alignment as reference Mahoney et al [28] 2020 Both RATKA and mTKA utilised mechanical alignment as reference for all except nine cases of two centers that were targeted within ± 3 degrees Marchand et al [30] 2017 RATKA: the prosthesis was manipulated allowing for optimal balancing and realignment. The knee was brought into extension, and alignment was checked with the robotic-assisted device both in extension and at 90 degrees of flexion No mention if mechanical/kinematic alignment was utilised to check the knee in extension mTKA: measured resection techniques used with mechanical alignment as reference Smith et al [49] 2019 RATKA: equal gap measurements within 1 mm between the flexion and extension gaps and the medial and lateral gaps, keeping limb alignment within 3 degrees of the mechanical axis and use the bone cuts to balance gaps instead of soft tissue releases unless the target fell out of 3 degrees window, at which point a combination of bone cuts and soft tissue releases was utilized to achieve balanced gaps within 1 mm Restricted kinematic alignment and gap balancing techniques mTKA: Mechanical alignment and measured resection techniques utilised Sultan et al [51] 2019 RATKA: Intraoperative adjustments to the plan were performed to determine ideal component placement for a balanced knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Robot group, it is significant that the rotation angle of the femur is determined in consideration of the soft tissue balance. Mahoney et al [44] revealed that the robotic-arm assisted TKA using MAKO demonstrated greater accuracy for tibial component alignment, femoral component rotation and tibial slope and provided greater three-dimensional accuracy to plan for various component positioning parameters.…”
Section: Tablementioning
confidence: 99%
“…Robotic-assisted TKAs have been shown to improve the accuracy and the precision of component placement compared with conventional jig-based procedures. [4][5][6] In addition, improved soft-tissue protection has been demonstrated with these techniques. 7 In a study comparing 40 patients who underwent manual TKAs to 40 who received robotic-assisted, the latter group was found to have decreased pain scores, improved early functional recoveries, and shorter LOS.…”
mentioning
confidence: 99%